ANALISIS PENGELOLAAN KEUANGAN DESA BERDASARKAN PERMENDAGRI NOMOR 20 TAHUN 2018 TAHUN ANGGARAN 2024 (STUDI KASUS: DESA SUKOREJO KECAMATAN BANGSALSARI KABUPATEN JEMBER) - Ulum, Misbahul; Mujib, Abdul; Asfufi, Nanang (E-Jurnal Akuntansi TSM, 2025)
This study aims to analyze the compliance of village financial management in Sukorejo Village, Bangsalsari District, Jember Regency for the 2024 fiscal year based on the Ministry of Home Affairs Regulation Number 20 of 2018. The method used is a qualitative descriptive approach with data collection techniques including observation, interviews, and documentation. The results indicate that village financial management in Sukorejo generally complies with applicable regulations, covering the planning, implementation, administration, reporting, and accountability stages. However, several discrepancies were found during the implementation and reporting stages, such as delays in submitting activity realization reports and reliance on the SISKEUDES application network. This study recommends improving the capacity of village officials and enhancing information systems to support transparent and accountable village financial governance.